One unit or more? One-year survival after red blood cells transfusion in stable emergency patients: a retrospective study - Fabien Coisy; Kevin Sourigues; Florian Ajavon; Céline Occelli; Alberto Di Castri; Xavier Bobbia; Romain Genre Grandpierre (BMC Emergency Medicine, 2026)
Abstract Background The management of anemia in hemodynamically stable emergency department (ED) patients frequently involves transfusion of red blood cells units (RBCs), although the benefit of administering more than one unit at a time remains uncertain. Current recommendations advocate a “single-unit” strategy, but evidence supporting long-term outcomes in the ED is limited. This study aimed to assess whether transfusion of more than one RBC unit in the ED impacts one-year mortality in stable anemic patients. Methods We conducted a retrospective, observational, single-center study including adult patients who received at least one non-emergency RBC transfusion in the ED between 2020 and 2022. Patients with hemorrhagic shock, massive bleeding, urgent transfusion orders, or chronic transfusion-dependent hematologic disease were excluded. The primary endpoint was one-year mortality. Survival was assessed using Kaplan–Meier analysis and Cox proportional hazards modeling adjusted for age, sex, Charlson index, hemoglobin level at admission, and hospitalization. A propensity score–matched analysis served as a sensitivity analysis. Secondary outcomes included factors associated with receiving > 1 RBC unit and early adverse events. Results Among 338 included patients, 93 (28%) received 1 RBC unit and 245 (72%) received > 1 RBC units. At one year, 35 (38%) and 78 (32%) patients had died in the 1 RBC and > 1 RBC units groups, respectively. Adjusted Cox analysis showed no association between transfusion of > 1 unit and one-year mortality (aHR 0.99; 95% CI: 0.63–1.56; p = 0.98). In the matched cohort, the hazard ratio was 0.91 (95% CI: 0.52–1.59). Lower hemoglobin levels were the main factor associated with receiving > 1 unit (aOR 0.33 per g/dL; p < 0.01). Conclusion In hemodynamically stable anemic patients managed in the ED, transfusing more than one RBC unit was not associated with a difference in one-year mortality compared with transfusion of a single unit. Further studies are needed to determine the optimal red blood cell transfusion strategy for ED patients.